AUSTRALIA'S SECURITY IN CHINA'S SHADOW - Graham, Euan. ([S.l.] : ROUTLEDGE, 2023)
A major shift in the paradigm undergirding relations between Australia and China has become clear in the early 2020s, with geopolitical concerns trumping economic considerations. Canberra has implemented a range of new policies in response to the risks it perceives in Australia's economic relations with China, the Chinese Communist Party's efforts to exert political influence in Australia, the expanding capabilities and presence of the People's Liberation Army, and Beijing's economic and diplomatic gains in Southeast Asia and the Southwest Pacific. China's policies towards Australia have become more coercive in economic as well as diplomatic terms. However, Australia has withstood Beijing's punitive trade measures without suffering significant economic damage. China's more assertive regional posture has prompted far-reaching changes to Australia's defence and alliance policy settings, including new capability acquisitions and strategic initiatives such as AUKUS. In this Adelphi book, Euan Graham argues that Australia has provided an imperfect but nevertheless useful exemplar of how governments may respond effectively to multifarious security challenges from China. In particular, the Australian case shows how measures to address domestic vulnerabilities may serve as the foundation for a successful China policy at the international level.
Keywords: HISTORY / Military / Strategy; POLITICAL SCIENCE / International Relations / General; POLITICAL SCIENCE / Political Freedom & Security / International Security; National security -- Australia; Australia -- Foreign relations -- China; China -- Foreign relations -- Australia